+ Que 20 ans après : Gesammelte Wörter und Bilder - Folie, Sabine; Generali Foundation, Wien; Genzmer, Synne; Zahradnik, Aneta; Lafer, Ilse (Berlin : Sternberg Press, 2015)
Auderer, Klaus ; Baumgarten, Lothar ; Broodthaers, Marcel ; Caramelle, Ernst ; Cha, Theresa Hak Kyung ; Dakic, Danica ; Downsbrough, Peter ; Dujourie, Lili ; Dunst, Heinrich ; Farocki, Harun ; Fisher, Morgan ; Fliri, Michael ; Fritscher, Susanna ; Gabellone, Giuseppe ; Ganahl, Rainer ; Graham, Rodney ; Grossarth, Ulrike ; Jacob, Luis ; Janssens, Ann Veronica ; Kasten, Barbara ; Koester, Joachim ; Kozlowski, Jaroslaw ; Litschauer, Maria Theresia ; Mallarmé, Stéphane ; Maloberti, Marcello ; Melitopoulos, Angela ; Lazzarato, Maurizio ; Morton, Ree ; Murphy, John ; Van Oldenborgh, Wendelien ; Oorebeek, Willem ; Oppermann, Anna ; Poledna, Mathias ; Pandian, Karthik ; Pumhösl, Florian ; Scherübel, Klaus ; Steiger, Dominik ; Steinbrecher, Erik ; Van Der Straeten, Andrea ; Strau, Josef ; Torfs, Ana ; Tscherkassky, Peter ; Tuerlinckx, Joëlle ; Voerman, Rob ; Wallace, Ian ; Willats, Stephen ; Zobernig, Heimo
boek